PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN ASSET, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PERUSAHAAN COSMETICS AND HOUSEHOLD DI BURSA EFEK INDONESIA - Safitri Ana Marfuah dan Siti Nurlaela (Jurnal Akuntansi dan Pajak, 2017)
Capital markets are trading activity related to capital, such as bonds and securities. This market serves to connect investors, companies and government institutions through long-term financial instruments trading. Capital structure decisions are not thorough and will result in high capital that will be received by the company and will affect the decline in profitability, it will threaten the company's financial position. This study has the objective to determine whether there is influence between the size of the company (firm size), the growth of assets (assets growth), profitability (return on equity) and sales growth (sales growth) on the capital structure (debt equity ratio) on a company to go public namely in the sectors listed Cosmetics and Houshold Indonesia Stock Exchange (BEI). The method used is quantitative, meaning researchers will quantify all of the data obtained. The samples used in this study 6 companies with the financial statements between 2010 to 2015. The sampling method in this research is purposive sampling with criteria in accordance with the objectives of the study. Analysis of the data used in this study using a method that consists of classic assumption test, multiple linear regression analysis, and test the hypothesis that simultaneous partial test and test. Results obtained from the partial test showed that the variables significantly influence the size of the company's capital structure. Asset growth variable has no significant effect on the capital structure. Variables significantly affect the profitability of capital structure. Variable sales growth known to have no significant effect on the capital structure. While the results obtained from testing simultaneously is the independent variable (the independent variable) used in this study (size of companies, growth in assets, profitability, sales growth) have a significant effect on the dependent variable (variable binder) that the capital structure.Keywords: firm size, asset growth, profitability, sales growth.